An analytical foundation of the ratio-dependent predator-prey model - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2004)
Predator-prey models of the Lotka-Volterra type and their refinements describe predator-prey interactions taking populations as basic units of analysis. In contrast to these macro models we derive interdependent population growth functions of a predator and a prey species from a micro ecosystem model whose basic entities are representative prey and predator organisms which behave as if they maximize their net offspring under constraints. In the short-run periods prices (scarcity indicators) coordinate and determine all biomass transactions and net offspring which directly translates into population growth and thus constitutes the dynamics of the predator-prey relations. For a specific parametric version our model offers a theoretical foundation of the ratio-dependent predator-prey model with Michaelis-Menten type functional response.
Keywords: 330; predator; prey; ratio-dependence; Bioökonomik; Theorie; Räuber Beute Modell